Analysis of students’ quantitative literacy in human coordination system concept - Yuda Harianto; Saefudin Saefudin; Eni Nuraeni (Universitas Sebelas Maret, 2017)
This study aimed to measure and analyze students’ quantitative literacy (QL) in human coordination system concept. It involved 76 participants (16-17 years old) from the second grade of senior high school at two national schools in Subang, West Java, Indonesia. These participants consisted of 39 males and 37 female students. Their QL was assessed by four essay tests to examine their QL indicators including interpretation, representation, calculation, and analysis through coordination system in human issue. Their answers were analyzed by a QL rubric according to Association of American Colleges and University (AACU) assessment. QL achievement for each indicator was categorized into four levels. The analysis result showed that students’ interpretation, representation, calculation, and analysis were at level 3, 2, 3, and 1, respectively. Based on data analysis, students’ achievement in calculation, interpretation, and representation were categorized as the milestone (mediocre). Meanwhile, their analysis skill was classified as a benchmark or the lowest QL level.